De-oxygenation of CO2 by using Hydrogen, Carbon and Methane over Alumina-Supported Catalysts - R. Y. Raskar; K. B. Kale; A. G. Gaikwad (Bulletin of Chemical Reaction Engineering & Catalysis, 2012)
The de-oxygenation of CO2 was explored by using hydrogen, methane, carbon etc., over alumina supported catalysts. The alumina-supported ruthenium, rhodium, platinum, molybdenum, vanadium and magnesium catalysts were first reduced in hydrogen atmosphere and then used for the de-oxygenation of CO2. Furthermore, experimental variables for the de-oxygenation of CO2 were temperature (range 50 to 650 oC), H2/CO2 mole ratios (1.0 to 5), and catalyst loading (0.5 to 10 wt %). During the de-oxygenation of CO2 with H2 or CH4 or carbon, conversion of CO2, selectivity to CO and CH4 were estimated. Moreover, 25.4 % conversion of CO2 by hydrogen was observed over 1 wt% Pt/Al2O3 catalyst at 650 oC with 33.8 % selectivity to CH4. However, 8.1 to 13.9 % conversion of CO2 was observed over 1 wt% Pt/Al2O3 catalyst at 550 oC in the presence of both H2 and CH4. Moreover, 42.8 to 79.4 % CH4 was converted with 9 to 23.1 % selectivity to CO. It was observed that the de-oxygenation of CO2 by hydrogen, carbon and methane produced carbon, CO and CH4. © 2012 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)